Normative Problems of the Criminal Elimination of Children Under 12 Years Against Principle of Equality Before The Law - SHIRA CASTA AURELLIA Shira Casta Aurellia; Yuliana Yuli Wahyuningsih Yuliana Yuli Wahyuningsih (KRTHA BHAYANGKARA, 2024)
This research is intended to examine the existence of criminal sanctions against children under the age of 12 as criminals and how there are regulations that confirm that they cannot be held a criminal responsibility. This gives rise to the view that the Principle of Equality Before the Law is not fulfilled. The transformation of the times has resulted in more and more criminal acts occurring so it does not rule out the possibility that similar things can be done by children under the age of 12. Therefore, it is necessary to carry out legal efforts related to punishment and criminal responsibility for children under the age of 12 who are proven to have done criminal acts (Strafbaarfeit) which are intended as an effort to re-function and learn for children so that justice, equality and legal certainty are met. In studying it, this research uses normative legal research methods and interprets it using prescriptive analysis techniques, namely regarding the study, especially of the Article on the elimination of criminal law as regulated in Article 21 paragraph 1 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and the Article on the elimination of responsibility by Child Offenders, which is regulated in Article 40 of Law Number 1 of 2023 concerning the Criminal Code and is linked to the principle of equality before the law.